Use and disposal of medicines from the family medicine cabinet through environmental education - Reyes-Diaz, María Gilda (2023)
The objective of the study was to describe the use and disposal of medicines from the family medicine cabinet from the perspective of environmental education. The study was conducted from January to October 2022 with 72 students of the Pharmacy and Biochemistry academic program of the Universidad Nacional “San Luis Gonzaga”, Ica, Peru. A virtual survey was applied using Google form with nine questions where the descriptive statistician was the relative trend analysis of the percentage. Storage in the medicine cabinet represented the highest percentage: 46.94%. The 10.20% of students did not know that medicines contaminate and 18.37% did not know that medicine wastes are harmful to health when consumed by animals and transferred to humans. A total of 6.12% of the students did not know that there are medicine containers and 14.29% of the students disposed of medicines inappropriately at home, where the highest percentage of disposal was for expiration and non-consumption: 46.94%. Annual disposal was the highest percentage (42.86%) and is produced by crushing (95.92%), where antibacterials were the therapeutic group with the highest frequency of disposal (46.95%) and antibiotics the lowest (2.04%). It is concluded that it is necessary to implement an environmental education on the disposal and elimination of medicines from the family medicine cabinet for university students, since there was a lack of knowledge about their storage, elimination and impact on public health and the environment.